A new method for estimating heat flux in superheater and reheater tubes - Purbolaksono J.; Khinani A.; Rashid A.Z.; Ali A.A.; Ahmad J.; Nordin N.F. (2023)
In this paper a procedure on how to estimate the heat flux in superheater and reheater tubes utilizing the empirical formula and the finite element modeling is proposed. An iterative procedure consisting of empirical formulae and numerical simulation is used to determine heat flux as both temperature and scale thickness increase over period of time. Estimation results of the heat flux over period of time for two different design temperatures of the steam and different heat transfer parameters are presented. 2009 Elsevier B.V. All rights reserved.